Prevention and treatment of tooth hypersensitivity in children and teenagers - I. A. Khoschevskaya (Медицинский совет, 2013)
In dentistry, as in any other area of medicine, pain, unfortunately, is often the only reason for visiting a doctor. Pain is referred to as "watchdog" of health, as it turns on self-preservation instinct and person starts doing something. The most common dental diseases are accompanied by an ache (caries and its complications, periodontal and oral mucosa diseases) caused by obvious dental tissue defect, inflammation or soft tissue oedema. Intense pain without obvious external reasons should be given special attention.